Development of Android apps for antenna analysis - Saleem, Amitha (2018)
The antenna is a translational device that is essential for any wireless communication system. There are several antenna designs that have been proposed over the last few decades and are used extensively in many applications. It is necessary to understand the antenna fundamental performance parameters to optimize and implement the antenna for a particular application. Various software tools such as MATLAB, ANSYS HFSS have been widely used to calculate these parameters. These tools are either expensive and require high capacity processor and computation time. Therefore, we have developed an android application that computes antenna fundamental performance parameters for different antenna types and plots 2D radiation pattern. The application is developed to serve as a learning and research tool for antenna design and as a reference and guidance document for the future work in this field. The results obtained from the developed android application is compared with the MATLAB simulation and validated.